Pengembangan Mesin Pengupas Biji Kopi Basah Skala Rumah Tangga Dengan Pemisahan Biji Terkupas Dan Tidak Terkupas Berdasarkan Ukuran Diameter Biji Kopi - Affandi, Bagus Rizal; Wulandari, Diah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Wet coffee bean processing at the household-scale farmer level is still largely carried out manually, requiring considerable time and labor while producing non-uniform bean quality. The use of wet coffee bean hulling machines is expected to improve post-harvest processing efficiency; however, in practice, several problems are still encountered, particularly in the coffee bean separation system. This study aims to design, construct, and test the performance of a household-scale wet coffee bean hulling machine and to analyze the performance of the separation system between hulled and unhulled coffee beans.The research method used was Research and Development (R&D), which included the stages of design, fabrication, and performance testing. The machine was designed using a single-phase electric motor with a power rating of 1 HP, a pulley and V-belt transmission system, a friction-based hulling mechanism, and a perforated screen as the coffee bean separation medium. Performance testing was conducted using post-harvest wet coffee beans at a shaft rotational speed of 420 rpm. The observed parameters included the machine’s ability to perform the hulling process and the hulling process time.The test results show that the wet coffee bean hulling machine is capable of performing the hulling process at a shaft rotational speed of 420 rpm and operates stably during the testing process. The coffee bean separation system functions in accordance with the design principles and is able to support wet coffee bean processing at the household scale. Based on the test results and analysis, the developed wet coffee bean hulling machine can be used as a supporting tool for household-scale wet coffee processing and has the potential for further development to improve performance and the effectiveness of post-harvest coffee processing.